Employers' perception of the costs and the benefits of hiring individuals with autism spectrum disorder in open employment in Australia - Scott, Melissa; Jacob, Andrew; Hendrie, Delia; Parsons, Richard; Girdler, Sonya; Falkmer, Torbjorn; Falkmer, Marita (Public Library of Science, 2017)
Research has examined the benefits and costs of employing adults with autism spectrum disorder (ASD) from the perspective of the employee, taxpayer and society, but few studies have considered the employer perspective. This study examines the benefits and costs of employing adults with ASD, from the perspective of employers. Fifty-nine employers employing adults with ASD in open employment were asked to complete an online survey comparing employees with and without ASD on the basis of job similarity. The findings suggest that employing an adult with ASD provides benefits to employers and their organisations without incurring additional costs.